(untitled) (Педагогіка вищої та середньої школи, 2009)
It is examined the contribution of Kyrylo Turovskiy, an outstanding thinker of the XIIth century, into the development of native mother country pedagogical science. Tyrovskiy thoughts about a man in general, his mental and moral abilities are analyzed as well in this article.